Doing Bahnhofsmission methodische Überlegungen zur empirischen Erforschung einer diakonischen Praxis - Siegl, Christine 1986- (2021)
An empirical study of the current practice of "Bahnhofsmission" requires a research strategy that succeeds in taking the diversity of individual places and activities seriously. The ethnographic approach seeks out people in the execution of their practices and accompanies them over a longer period of time. The praxeological research perspective understands practice as a sensual human activity that is characterised by materiality, corporeality and temporality. This approach succeeds in depicting "doing Bahnhofsmission" as a concatenation of diverse social practices.